Navigating Uncertainty: Health Professionals' Knowledge, Skill, and Confidence in Assessing and Managing Pain in Children with Profound Cognitive Impairment. (21st December 2016) - Carter, Bernie; Simons, Joan; Bray, Lucy; Arnott, Janine
Abstract : There is limited evidence to underpin the assessment and management of pain in children with profound cognitive impairment and these children are vulnerable to poor pain assessment and management. Health professionals working with children with profound cognitive impairment from a single paediatric tertiary referral centre in England were interviewed to explore how they develop and acquire knowledge and skills to assess and manage pain in children with cognitive impairment. The interviews were transcribed and subjected to thematic analysis. Nineteen health professionals representing different professional groups and different levels of experience participated in the study. A metatheme "navigating uncertainty; deficits in knowledge and skills" and two core themes "framing as different and teasing things out" and "the settling and unsettling presence of parents" were identified. Uncertainty about aspects of assessing and managing the pain of children with cognitive impairment tended to erode professional confidence and many discussed deficits in their skill and knowledge set. Uncertainty was managed through engaging with other health professionals and the child's parents. Most health professionals stated they would welcome more education and training although many felt that this input should be clinical and not classroom oriented.